Veno-venous extracorporeal membrane oxygenation application for patient with acute lung injury due to rhabdomyolysis; a case report - Dongsub Noh; Yong Han Cha (Trauma Case Reports)
A 47-year-old male patient, who underwent open reduction and internal fixation with plate for a Gustilo-Anderson type II open proximal tibiofibular fracture of the right lower leg, experienced rhabdomyolysis. Rapid progression of acute respiratory distress syndrome and acute renal failure occurred due to rhabdomyolysis. After veno-venous extracorporeal membrane oxygenation, he exhibited a relatively smooth clinical recovery. Our case report suggests that circulating cytotoxic substances from rhabdomyolysis resulted in concomitant acute respiratory distress syndrome and acute renal failure. This case was successfully treated after applying extracorporeal membrane oxygenation.